EEFDA: enabling efficient and fault-tolerant data aggregation scheme without TA in smart grid - Yuanyuan Wang; Liqiang Wu; Yiliang Han; Xuguang Wu; Ruifeng Li (Complex & Intelligent Systems)
Abstract Smart grid can be effectively enhanced by user data, however, data breaches pose significant risks related to privacy violations and data misuse. To address this issue, fault-tolerant privacy-preserving data aggregation schemes can protect data privacy while accommodating user drops. Most existing solutions depend on auxiliary computation in trusted authority for data aggregation. However, for practical smart grid applications, it is often unrealistic to expect these centers to remain online at all times. Designing a solution that does not rely on trusted authority (TA) while ensuring fault tolerance is a challenging task. In this paper, we propose an enabling efficient and fault-tolerant data aggregation scheme without TA, named EEFDA. Unlike existing encryption schemes, EEFDA supports reusable masks. We introduce the Reusable Shamir Threshold Secret Sharing (RSSS) technique, which allows users to securely adjust the secret without disclosing the initial sharing. The EEFDA scheme not only enhances system robustness but also reduces the communication overhead for inter-user interactions. Numerous experiments demonstrate that EEFDA communication is low-cost, efficient, and well-suited for resource-constrained devices.